Política de formação de professores para educação bilíngue de surdos - Lima, Marcia Dias (2024)
This PhD research is associated with the Post-Graduation Program in Education at the Federal University of Uberlândia, in the research line “Estado, Políticas e Gestão da Educação” (State, Policies and Education Management), and it takes part in the policies for the teacher’s formation issues with the theme: “TEACHER FORMATION POLICIES FOR BILINGUAL EDUCATION FOR THE DEAF”. In this sense, the main objective was to analyze the public policies and the orientation of the legal texts about teachers’ formation towards Education for the Deaf in the period from 2002 to 2022. The study’s specific objectives were: to discuss the policy of deaf education from the cultural studies’ perspective; to discourse about how Education for the Deaf was configured in Brazil; to explain how Deaf students teachers’ formation takes place in Brazil; to describe how teachers’ formation policies contemplate the teachers’ formation for Bilingual Education for the Deaf, to present guide principles to elaborate a new proposal for Deaf students teachers’ formation in a bilingual perspective. The methodology used in this research was configured as qualitative and exploratory, involving, mainly, documental analysis. In this context, the research’s main hypothesis was that the teachers’ formation policy for Education for the Deaf, as established in the Brazilian regulatory documents from 2002 to 2022, is inadequate since it does not prepare teachers in theory and practice to work effectively in the school modality of Bilingual Education for the Deaf. The results revealed that the graduation courses do not properly support the legal requirements for Bilingual Education for the Deaf. It is possible to observe an isolated interest in educational and linguistic issues related to the Deaf by teachers and researchers. Thereby, it is recommended to implement actions that include sign language analysis, cultural studies, dialogue with the Deaf community and reflection about the fundamentals of an education that values the Deaf language, identity and culture. It is important to promote the autonomy of the teachers, by means of formation that allows an integrative and less structured approach. The bilingual approach is crucial to reducing the linguistic gap and strengthening the Deaf students capacity to understand complex concepts and fully participate in the school curriculum. In face of it, it is suggested a continued and collaborative strategy between theory and practice and a reflection in the teacher's formation. The formation policy should include clear guidelines, the development of specific curricula, financial resources’ guarantee, institutional collaboration, continuous monitoring and research encouragement. The initial formation and the continued formation still need efficient State policies that, actually, prepare teachers for the reality of Bilingual Education for the Deaf. Moreover, this study concluded that Brazilian policies of teachers’ formation for Deaf education do not properly prepare teachers to act in the Bilingual Education for the Deaf modality, both theoretically and in practice. In the end, it is necessary to emphasize the necessity of a critical review of current policies and the implementation of clear guidelines, specific curriculum development and the encouragement to institutional collaboration in order to promote a more inclusive and efficient education for the Deaf community.